Repositioning the Caribbean within globalisation - Payne, Anthony (The Centre for International Governance Innovation WaterlooCA, 2007)
Examines three key policy agendas viz. competitiveness, diplomacy and governance. Provides an overview of the main issues in each case which sets the particular circumstances of the Commonwealth Caribbean within wider global development. Focuses on the current 'state of policy' in each area, highlights progress made and problems encountered. Discusses policy issues and identifies both key concerns in current policy and urgent policy questions that still remain to be resolved. Concludes that real progress can be made only if the Commonwealth Caribbean adopts the 'functional equivalent' at the regional level of the kind of 'development state' that was so successful in East Asia. Suggests that this will involve restructuring CARICOM to become more innovative, proactive and directive than has been the case to date.